The Application and Research of Self made Air Cushion made by Rubber Balloon in the Prevention of Pressure Sore in Clinical Operation. (2021) - Xiu-jun, LIANG; Ju-hua, TAN; Yu, LI; Yan, LU; Ping-hua, WU; Zhong-yu, LIU; Ting, HUANG; Ren, JING
No abstract available